1991
DOI: 10.1557/jmr.1991.0514
|View full text |Cite
|
Sign up to set email alerts
|

Pulse laser processing of a SiC/Al-alloy metal matrix composite

Abstract: The microstructural changes and the tensile behavior of laser processed A356-A1 alloy matrix composites reinforced with 10 and 20 vol. % SiC particulates are characterized. The autogenous bead-on-plate welds were made using a pulsed CO 2 laser operating at a peak power level of 3.2 kW. The pulse on-time was constant at 20 ms and the off-time was varied from 20 to 2 ms (duty cycles of 50-91%). The microstructure of the laser melted region was investigated by optical, scanning, and transmission electron microsco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…As a result, Al 4 C 3 and Al 4 SiC 4 may also precipitate directly from the C and Si enriched Al-based melt formed [12]. The presence of Al 4 Si 2 C 5 carbide has been reported by Dahotre et al [13] in pulsed laser welding of SiC/Al-alloy composites and by Liechti [14] that observed the presence of both Al 4 SiC 4 and Al 2 SiC 5 in Al-Si/SiC coatings produced by laser cladding. However, Al 4 Si 2 C 5 was not found in the detailed and extensive study carried out by Viala et al [6] and Oden et al [12] and controversy exists about the formation of this carbide.…”
Section: Introductionmentioning
confidence: 66%
“…As a result, Al 4 C 3 and Al 4 SiC 4 may also precipitate directly from the C and Si enriched Al-based melt formed [12]. The presence of Al 4 Si 2 C 5 carbide has been reported by Dahotre et al [13] in pulsed laser welding of SiC/Al-alloy composites and by Liechti [14] that observed the presence of both Al 4 SiC 4 and Al 2 SiC 5 in Al-Si/SiC coatings produced by laser cladding. However, Al 4 Si 2 C 5 was not found in the detailed and extensive study carried out by Viala et al [6] and Oden et al [12] and controversy exists about the formation of this carbide.…”
Section: Introductionmentioning
confidence: 66%
“…This shows that the energy density plays an important role in the deterioration of reinforcements. In addition, other work has shown that, even in laser welds with a high energy density, [4,24] pulsing will reduce the tendency toward the formation of carbides. Since the peak temperature of the molten pool is related to the energy density, one can envision that the deterioration is directly linked to the temperatures achieved in the weld pool.…”
Section: A Deterioration Of Reinforcements In Fusion Weldsmentioning
confidence: 99%
“…[1,2] In the past, fusion welding, diffusion bonding, resistance welding, and friction welding have been used to evaluate the feasibility of joining these materials. [1][2][3][4][5][6][7][8][9][10][11][12][13] Among the fusion-welding processes, the arc, electron beam (EB), and laser beam (LB) methods have been considered, with and without filler wire. Resistance spot welding was performed, with and without a soft aluminum interlayer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Authors have also carried out an autogenous bead-onplate welding experiment of A356 alloy reinforced with SiCp 10 and 20 vol% using pulsed CO 2 laser at 3.2 kW peak power to study the microstructure and determine the mechanical properties of the weldment. Dahotre et al [19], in their study carried out mechanical testing using Instron tensile testing machine. Both optical microscopy and analytical electron microscopy were used for microstructure characterization.…”
Section: Investigation On Al-sic MMCmentioning
confidence: 99%